Interactions between microglia and glioma in tumor microenvironment - Tao, Jin-Cheng; Yu, Dong; Shao, Wei; Zhou, Dong-Rui; Wang, Yu; Hou, Shi-Qiang; Deng, Ke; Lin, Ning (Frontiers in Oncology, 2023)
Gliomas, the most prevalent primary tumors in the central nervous system, are marked by their immunosuppressive properties and consequent poor patient prognosis. Current evidence emphasizes the pivotal role of the tumor microenvironment in the progression of gliomas, largely attributed to tumor-associated macrophages (brain-resident microglia and bone marrow-derived macrophages) that create a tumor microenvironment conducive to the growth and invasion of tumor cells. Yet, distinguishing between these two cell subgroups remains a challenge. Thus, our review starts by analyzing the heterogeneity between these two cell subsets, then places emphasis on elucidating the complex interactions between microglia and glioma cells. Finally, we conclude with a summary of current attempts at immunotherapy that target microglia. However, given that independent research on microglia is still in its initial stages and has many shortcomings at the present time, we express our related concerns and hope that further research will be carried out to address these issues in the future.